Nocebo Effect in Randomized Clinical Trials of Antidepressants in Children and Adolescents: Systematic Review and Meta-Analysis - Rojas-Mirquez, Johanna Carolina; Rodriguez-Zuñiga, Milton Jose Max; Bonilla-Escobar, Francisco Javier; Garcia-Perdomo, Herney Andres; Petkov, Mike; Becerra, Lino; Borsook, David; Linnman, Clas (Frontiers in Behavioral Neuroscience, 2014)
Objective: To compare the incidence of adverse events between active and placebo arms of randomized clinical trials in depressive children and adolescents with antidepressant treatments, in order to look for similarities in both groups that allow to establish a possible nocebo effect. Methods: Systematic search strategy (January 1974-March 2013) in electronic databases, conference abstracts and reference list of systematic reviews and included studies to identify parallel randomized placebo-controlled trials of antidepressants in children and adolescents (<19 years) with Major Depressive Disorder, and one or more interventions of any orally administered antidepressant. The pooled adverse events were calculated based on a fixed-effect model and statistical analysis involved the Risk Ratio (RR) of adverse events, with 95% confidence intervals (95%CI). Results: Sixteen studies were included in the review, of which seven studies with a sample of 1911 patients had data to include in the meta-analysis. There was similar risk for the incidence of adverse events between non-active and active group (global Risk Ratio 1.04, 95% Confidence Interval: 0.97-1.11). Conclusions: Depressive children and adolescents allocated to placebo or active group had similar risk to develop adverse events. These similarities in both groups are attributed to the nocebo effect. It is of note that defining "nocebo" effects is challenging in clinical populations because adverse effects may be attributed to the intervention or may be manifestation of the disease itself. The inclusion of a no treatment arm may be warranted. Nocebo effects are likely when adverse events of placebo mimic the adverse events of active treatment, as was the case here.